2020
DOI: 10.3390/su12219289
|View full text |Cite
|
Sign up to set email alerts
|

Envisaging Mitigation Action Can Induce Lower Discounting toward Future Environmental Gains and Promote Pro-Environmental Behavior

Abstract: Low engagement with climate change may stem from the tendency to discount the distant benefits of mitigation action. Hence, a reduced tendency to discount the future should be associated with increased involvement in climate change mitigation. Prior research has demonstrated that episodic future thinking (EFT; i.e., envisioning future events that involve self-projection) can reduce discounting. In two laboratory studies, we showed that engaging in EFT about mitigation action was associated with a lower discoun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
6
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 58 publications
0
6
0
1
Order By: Relevance
“…For this purpose, the use of episodic future thinking about income shocks, which consists in projecting the self into the future to pre-experience a positive or negative income shock, has proven its efficacy to shift temporal discounting (Bickel et al, 2016;Sze et al, 2017). Similarly, some studies have shown that engaging in episodic future thinking about climate change-related risks and climate change mitigation leads to acting pro-environmentally (Ho et al, 2020;Lee et al, 2020). Future research could assess whether episodic future thinking about income shocks has a similar effect on pro-environmental behaviour, and whether this effect is partially mediated by temporal discounting.…”
Section: Discussionmentioning
confidence: 99%
“…For this purpose, the use of episodic future thinking about income shocks, which consists in projecting the self into the future to pre-experience a positive or negative income shock, has proven its efficacy to shift temporal discounting (Bickel et al, 2016;Sze et al, 2017). Similarly, some studies have shown that engaging in episodic future thinking about climate change-related risks and climate change mitigation leads to acting pro-environmentally (Ho et al, 2020;Lee et al, 2020). Future research could assess whether episodic future thinking about income shocks has a similar effect on pro-environmental behaviour, and whether this effect is partially mediated by temporal discounting.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it was impossible to determine whether the effects shown were owing to pre-experience of future events or to thinking about the future. After correcting methodological flaws in 203 The effect of episodic future thinking on learning intention previous studies Ho et al, 2020;Wu et al, 2017), it was discovered that episodic future thinking strengthens learning intentions more than semantic future thinking. The comparison with semantic future thinking rather than non-future thinking, such as episodic present thinking, demonstrates the significance of pre-experience of future events.…”
Section: Discussionmentioning
confidence: 99%
“…This study examines the effects of episodic future thinking by comparing it with semantic future thinking. Such attempts have been made in previous studies Ho et al, 2020;Wu et al, 2017). However, those studies have methodological problems in which the procedures are asymmetrical between the conditions for episodic and semantic future thinking.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Selanjutnya, terhubung dengan EFT juga dapat memfasilitasi persepsi mengenai peristiwa masa depan dekat secara psikologis, sehingga meningkatkan risiko yang dirasakan terkait dengan peristiwa tersebut (Lee et al 2020). Hal ini juga didukung oleh penelitian Ho et al (2020) yang menyatakan bahwa terlibat dalam EFT untuk membayangkan peristiwa kehidupan yang melibatkan tindakan mitigasi menyebabkan peningkatan keterlibatan pribadi dalam perubahan iklim dan mempromosikan kecenderungan untuk melakukan tindakan pro-lingkungan.…”
Section: Diskusiunclassified